2019
DOI: 10.3389/fmicb.2019.02361
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Seven New Genomes of Xanthomonas citri pv. aurantifolii Strains, Causative Agents of Citrus Canker B and C, Show a Reduced Repertoire of Pathogenicity-Related Genes

Abstract: Xanthomonas citri pv. aurantifolii Genomes in pathogenicity-related subsystems. These subsystems, the Types I and IV Secretion Systems, and the Type IV pilus, therefore emerge as important ones in helping explain the aggressiveness of the A type of citrus canker and the apparent dominance in the field of the corresponding strain over the B and C strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Recently, a complete genome-based study demonstrated that the type B and type C strains lack genes involved with the types I and IV secretion systems, the biosynthesis of alginate, hemagglutinin and hemolysin, which are known to play a role in host infection in type A, the more aggressive haplotype (Fonseca et al 2019). This result is consistent with the attenuated citrus canker phenotypes of B and C variants.…”
Section: Xanthomonas Citri Pv Aurantifolii (Types B and C)mentioning
confidence: 54%
“…Recently, a complete genome-based study demonstrated that the type B and type C strains lack genes involved with the types I and IV secretion systems, the biosynthesis of alginate, hemagglutinin and hemolysin, which are known to play a role in host infection in type A, the more aggressive haplotype (Fonseca et al 2019). This result is consistent with the attenuated citrus canker phenotypes of B and C variants.…”
Section: Xanthomonas Citri Pv Aurantifolii (Types B and C)mentioning
confidence: 54%
“…Genes involved in copper/arsenate resistance and conjugation are highlighted along the plasmid sequences. Fonseca et al, 2019). Recently, with the availability of the longread sequencing method and the advances in genome assembly (Kolmogorov et al, 2019), complex genome structures can be fully resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequencing has been widely used to understand the pathogenic, taxonomic and phylogenetic status of the xanthomonads ( Zhang et al, 2015 ; Bansal et al, 2017 ; Patane et al, 2019 ). Previous studies lacked the resolution of repetitive or duplicate regions as they could not be precisely resolved by the short-read sequencing method and the bioinformatic algorithm ( Triplett et al, 2011 ; Fonseca et al, 2019 ). Recently, with the availability of the long-read sequencing method and the advances in genome assembly ( Kolmogorov et al, 2019 ), complex genome structures can be fully resolved.…”
Section: Discussionmentioning
confidence: 99%
“…citri after its detailed genomic investigation [ 23 , 25 , 27 ]. Similarly, the name of the causative agent of cancrosis B and C is usually published as Xanthomonas fuscans pv aurantifolii or Xanthomonas citri pv aurantifolii [ 30 , 31 ]. Here, we are abbreviating the causative agents of canker A, B, and C as Xcc, XauB, and XauC, respectively.…”
Section: Pathogen Profilementioning
confidence: 99%